A study of postdatism: its incidence and associated morbidities in a tertiary care centre: a prospective observational study - Miskin, Sneha; Palve, Tushar; Narvekar, Rutuja M.; Parasnis, Ketki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study shows the incidence of postdatism in a pregnancy, and to find out the incidence of maternal and fetal complications, perinatal mortality in postdated pregnancy. Methods: All registered ANC patients coming to OPD and labour ward completed 40 weeks of gestational age by date (who were sure of the date of last menstrual period) or by scan (considering early weeks scan) are considered in the study. History and examination of the patients are done and mode of delivery was decided accordingly. Fetal monitoring was done using non stress test, ultrasonography and DFKC charting maintained. Results: Postdatism is very common in primigravida (61%) than multigravida, and is common in age group of 21-30 years (67%), most common mode of delivery was vaginal delivery with approximately 30% undergoing LSCS due to various reasons. In perinatal assessment there was one IUFD and 5 NICU admissions in a total of 100 postdatism pregnancies. Maternal morbidities like sepsis, postpartum hemorrhage, perineal tear ivo shpulder dystocia and big baby will also be present in small number of cases. Conclusions: This study shows the incidence of postdatism according to gravida score and age factors. It also shows the associated perinatal and maternal morbidities in a patient with postdatism.